PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MENANGANI KRISIS KEMANUSIAAN DI SURIAH TAHUN 2012-2015 - Efissa Pratiwi; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explaining the role of ICRC in dealing with victims of the armed conflict in the Syria Arab Republic that began in 2011, between Assad government and rebel forces Syria. President Bashar Al-Assad protested by Syrian in March 2011. Assad government used armed forced to handle the demonstrations which led conflict started to blow up. Since the conflict began Syrian people faced situations that the risk their right. Civil, children were killed shot by the gun, explosive shelling, detention and bombing, the conflict itself affect the humanitarian crisis in Syria; damaged infrastructure, killed and injured were people syria, refugees, suffer from due lack to food and medicine.The research use pluralism perspective of International Relations. Pluralism believes that state is not the only actor in the international world. This research is also guided by international organization theory and role. The techniques used to collects data to study the case to library research in the form of journals, books, official document, article, and website. Formulation of all arguments, facts, and theoretical framework for this research is guided by qualitative explanation methods.ICRC has keep it focus a mission on behalf of helping the war victims during the conflict and the effect of the humanitarian crisis in Syria by aid food, providing clean water and upgrading sanitation water supply infrastructure, distributed hygiene kits, mats, rugs, blankets and winter clothing to the needs of millions of people affected by the conflict.Keyword: ICRC, armed conflict, the humanitarian crisis in Syria